Personalizing neoadjuvant chemotherapy for locally advanced colon cancer: protocols for the international phase III FOxTROT2 and FOxTROT3 randomized controlled trials. (15th February 2023) - Platt, James R.; Williams, Christopher J. M.; Craig, Zoe; Cairns, David A.; Glasbey, James C.; Morton, Dion; Seligmann, Jenny
Abstract: Aim: FOxTROT1 established a new standard of care for managing locally advanced colon cancer (CC) with neoadjuvant chemotherapy (NAC). Six weeks of neoadjuvant oxaliplatin and fluoropyrimidine (OxFp) chemotherapy was associated with greater 2‐year disease‐free survival (DFS) when compared with proceeding straight to surgery (STS). There is now a need to refine the use of NAC and identify those most likely to benefit. FOxTROT2 will aim to investigate NAC in older adults and those with frailty. FOxTROT3 will aim to assess whether intensified triplet NAC provides additional benefits over OxFp. Method: FOxTROT2 and FOxTROT3 are international, open‐label, phase III randomized controlled trials. Eligible patients will be identified by the multidisciplinary team. Patient age, frailty and comorbidities will be considered to guide trial entry. Participants will be randomized 2:1 to the intervention or control arm: 6 weeks of dose‐adapted neoadjuvant OxFp versus STS in FOxTROT2 and 6 weeks of neoadjuvant modified oxaliplatin, 5‐fluorouracil and irinotecan versus OxFp in FOxTROT3. The primary endpoint in FOxTROT2 is 3‐year DFS. In FOxTROT3, tumour regression grade and 3‐year DFS are co‐primary endpoints. Discussion: FOxTROT2 and FOxTROT3 will establish the FOxTROT platform, a key part of our long‐term strategy to develop neoadjuvant treatments for CC. FOxTROT2 will investigate NAC in a population under‐represented in FOxTROT1 and wider research. FOxTROT3 will assess whether it is possible to induce greater early tumour responses and whether this translates to superior long‐term outcomes. Looking ahead, the FOxTROT platform will facilitate further trial comparisons and extensive translational research to optimize the use of NAC in CC.